A {1,2,3,5,7,9,11,13} and B {1,2,4,6,8,12,13} verify the rule n(AUB) = n(A) + n(B) -n(AnB)​

Question

A {1,2,3,5,7,9,11,13} and B {1,2,4,6,8,12,13} verify the rule n(AUB) = n(A) + n(B) -n(AnB)​

in progress 0
Natalia 7 days 2021-09-10T21:16:45+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-10T21:17:53+00:00

    Answer:

    Step-by-step explanation:

    AUB= {1,2,3,4,5,6,7,8,9,11,12,13}

    n(AUB)=12=L.H.S

    A={1,2,3,5,7,9,11,13}

    n(A)=8

    B= {1,2,4,6,8,12,13}

    n(B)=7

    A∩B={1,2,13}

    n(A∩B)=3

    n(A) + n(B) -n(A∩B)​=8+7-3=12=R.H.S

    therefore, L.H.S=R.H.S

    hence verified

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )